Effects of non-initial radiation exposure on solid cancer mortality risk among Hiroshima A-bomb survivors - Ohtaki, Megu; Otani, Keiko; Hoshi, Masaharu; Yasuda, Hiroshi (Frontiers in Public Health, 2025)
PurposeExposure of atomic bomb (A-bomb) survivors to non-initial (residual) radiation and consequent health effects has not yet been reliably estimated. This study aimed to quantify the contribution of non-initial radiation to the increase in solid cancer mortality risk among A-bomb survivors in Hiroshima through a comparative analysis considering geographical factors.DataWe analyzed the data of 43,056 (17,603 men and 25,453 women) A-bomb survivors registered in the A-bomb Survivor Cohort Database (ABS) at Hiroshima University. These subjects were aged <50 years old at the time of the bombing and lived in Hiroshima Prefecture as of 1 January 1970, after being exposed within 5.0 km of the hypocenter.MethodsThe radiation doses and excess deaths from all solid cancers of the A-bomb survivors were estimated for districts geographically divided by distance and direction from the hypocenter. The dose was defined as the sum of the initial and non-initial radiation doses, and district-averaged non-initial doses were calculated. The excess relative risks (ERRs) of all solid cancer deaths were estimated using multivariate survival analysis with an additive parametric hazard model under the linear no-threshold (LNT) hypothesis. The γ-ray equivalent doses (Sv) from non-initial radiation were estimated based on the estimated ERRs.ResultsEstimated ERRs were notably higher west of the hypocenter than in the other directions. This trend increased with increasing distance from the hypocenter, and the ERRs in men were higher than those in women. Significantly higher ERR values of 52% (p < 0.01) for men and 29% (p < 0.05) for women were obtained at a distance of 2.0–2.5 km west of the hypocenter. The γ-ray equivalent doses estimated from these ERRs exceeded 2 Sv of the effective dose in men west of the hypocenter. This level was notably higher than the estimated initial radiation dose.ConclusionThe findings of this study highlight the considerable contribution of non-initial radiation to the health consequences of the A-bomb survivors. These effects are attributable to the radionuclides generated by the A-bomb detonation, which were assumed to be carried by the wind to the west and deposited with rain in the western region from the hypocenter.